2017
DOI: 10.1093/jac/dkx429
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner and nurse prescriber experiences of prescribing antibiotics for respiratory tract infections in UK primary care out-of-hours services (the UNITE study)

Abstract: BackgroundInterventions are needed to reduce unnecessary antibiotic prescribing for respiratory tract infections (RTIs). Although community antibiotic prescribing appears to be decreasing in the UK, figures for out-of-hours (OOH) prescribing have substantially increased. Understanding the factors influencing prescribing in OOH and any perceived differences between general practitioner (GP) and nurse prescriber (NP) prescribing habits may enable the development of tailored interventions promoting optimal prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 27 publications
5
76
0
1
Order By: Relevance
“…However, these studies have focused on antibiotic prescribing behaviour. Relationships with other prescribers and knowledge of current guidelines (Rowbotham et al, 2012;Williams et al, 2018), diagnostic uncertainty and the clinical condition of the patient (Abbo, Smith, Pereyra, Wyckoff, & Hooton, 2012;Adorka, Dikokole, Mitonga, & Allen, 2013;Rowbotham et al, 2012), in addition to patient expectations for a medicine (Adorka et al, 2013;Rowbotham et al, 2012), evidenced-based guidelines, experience and clinical complications (Philp & Winfield, 2010), peer and organizational support and patient contact (Offredy, Kendall, & Goodman, 2008) have each been reported as important influences.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…However, these studies have focused on antibiotic prescribing behaviour. Relationships with other prescribers and knowledge of current guidelines (Rowbotham et al, 2012;Williams et al, 2018), diagnostic uncertainty and the clinical condition of the patient (Abbo, Smith, Pereyra, Wyckoff, & Hooton, 2012;Adorka, Dikokole, Mitonga, & Allen, 2013;Rowbotham et al, 2012), in addition to patient expectations for a medicine (Adorka et al, 2013;Rowbotham et al, 2012), evidenced-based guidelines, experience and clinical complications (Philp & Winfield, 2010), peer and organizational support and patient contact (Offredy, Kendall, & Goodman, 2008) have each been reported as important influences.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“… 5–7 The interest in antibiotic prescribing in OOH care and possible corresponding interventions is growing internationally. 8–13 The results of earlier intervention studies show us a rather limited positive effect on antibiotic prescribing in size, quality and time. These observations evoke the hypothesis that top-down intervention might have only small results.…”
Section: Introductionmentioning
confidence: 99%
“… 20–23 When working on interventions to improve antibiotic prescribing, studying and reflecting on the specifics of the context and setting are important to come up with tailored bottom-up supported solutions. 8 22 24 25 To optimise the quality of GPs’ antibiotic prescribing behaviour in OOH care, a better understanding of the present attitudes as well as interventions that build on this knowledge is needed. Prescribing behaviour is about making a diagnosis and implementing a treatment plan, and about social interactions in a specific context.…”
Section: Introductionmentioning
confidence: 99%
“…Resources to support AMS should be promoted across the whole health economy, for example, community pharmacists, OOH staff, school nurses, care homes, as AMS leads reported mainly promoting TARGET leaflets and education to GP staff. Education across healthcare is important as OOHs and care homes are often reported as areas of greater prescribing [3,26], yet respondents in the present study reported that they were not supported as well as other groups. Monitoring uptake of initiatives could be facilitated through local engagement schemes, which over 70% of CCGs reported having [23], as practitioners have to provide evidence of how they meet the requirements of the scheme, such as attending AMS education/training.…”
Section: Implications For Nhs Commissioning Organisationsmentioning
confidence: 67%